Witnessing: The Axis of Group. Issue 1 (2nd January 2019) - Billow, Richard M.
ABSTRACT: We enter the group and, to some degree make choices in what we observe and focus on, and how we participate and make our presence known. Unavoidably, and with limited control, we are thrust into a public position of witness and witnessed. Witnessing deals with the impact of embracing experience beyond observing and participating–the uncertain consequence of coming to know and becoming known. It is specifically the axis of personal growth and transformation around which a dynamically oriented group process rotates with our leadership. Discussion and two case examples illustrate its key features and the role members and therapist play in fostering this process.